ESTUDO DA EXPRESSÃO DE RECEPTORES DE ADENOSINA EM RETINA - Pereira, Mariana Rodrigues (2009)
Adenosine is an important neuromodulator in CNS and its actions are promoted by activation of A1, A2a, A2b and A3 receptors. Previous studies from our laboratory have shown that A1 e A2 receptors are present in intact chick embryo retina. In culture, the detection of A1 receptor depends on cell aggregation. Monolayer cultures have shown a low or undetectable binding of A1 agonist 3(H)CCPA or antagonist 3(H)DPCPX. Chronic treatment with the permeable cyclic AMP analogs SpcAMP or 8 BrcAMP was able to increase receptor detection. In addition, forskolin also significantly increased the binding. These results suggest the modulation of A1 receptor detection via A2a receptor activation. A2a adenosine receptors are expressed in embryonic retinas starting at 7 days of development (E7) when the levels of receptor expression are higher. At E9 the level decreased about 45% and remained constant up to E16. This receptor was also finder in monolayer cultures. Treatment of cultures with the A2a agonist DPMA increased 3(H)DPCPX binding and this effect was completely blocked by H89, a PKA inhibitor. Treatment with A1 antagonist DPCPX or agonist CHA increased 3(H)DPCPX binding. In the same way, treatment with adenosine deaminase, EHNA or inosine increased the binding. The results indicate that the activation of A2a receptors modulates the expression of A1 receptors in chick retina cultures. In addition, the results suggest the participation of A3 receptors activated by inosine.